A Comparative Clinical Evaluation of Efficacy of Guduchi (Tinospora Cordifolia (Willd.) Miers) Kanda (Stem) and Gambhari (Gmelina Arborea Roxb.) Twak (Bark) in Vatarakta with special reference to Gouty Arthritis (AYUSHDHARA, 2023)
Vatarakta is caused due to Dushita vata and Dushita rakta which vitiate independently and also interdependently. They further lodge in the different Dhathu and manifest as Utthana or Gambhira vatarakta. Based on symptomology, Gambhira vatarakta can be co-related to gouty arthritis, a disorder of purine metabolism. Ayurvedic classics indicate many single herb and compound formulations in management of Vatarakta. Among them, Guduchi which has been mentioned as the Agrya dravya for Vatarakta, and Gambhari, which has been indicated as Vataraktahara by Bhavaprakasha Nighantu, have been selected for trial in this study. 40 subjects fulfilling the inclusion criteria were selected and randomly divided into two groups. Group A and Group B were given Guduchi kanda Kashaya and Gambhari twak Kashaya respectively, 40ml per day in two divided doses, before food, with Jala as Anupana, for a duration of 48 days. Sandhi shula, Sandhi daha, Sandhi shotha, and Sandhi stabdhata were considered as subjective parameters, and Serum Uric Acid levels and Erythrocyte Sedimentation Rate were taken as objective parameters. Assessment of these parameters was done before and after the intervention. Appropriate statistical tests were applied to analyse the results. Both groups showed marked improvement in the subjective and objective parameters which was statistically significant (p